Химический состав красных гигантов с магнитными полями: обзор последних результатов - Любимков, Л. С.
On the base of the series of works implemented recently in the Crimean astrophysical observatory the data are considered on the chemical composition of 20 G- and K-type giants with magnetic fields in comparison with the chemical composition of 7 non-magnetic giants. Substantial differences are found in the lithium abundance and in the [N/C] value between magnetic and non-magnetic giants: both these parameters are known to be sensitive indicators of star's evolution. It was shown that lithium is absent in almost all non-magnetic giants, that is in full accordance with the theory predictions concerning the evolution of giants, which passed through the deep convective mixing during the FDU phase. Conversely, for most magnetic giants lithium is present in an atmosphere. Further, the [N/C] value, when considered as a function of the age and the mass, shows systematic differences between magnetic and non-magnetic giants. Possible explanations are discussed of differences found for chemical composition of the two types of giants. It was shown that the total C+N+O abundance, which remains probably constant during the star's evolution, demonstrates a clear dependence on the metallicity index [Fe/H], and not only for the giants in question but also in the expanded region [Fe/H] from -2.5 to +0.3.
Keywords: Красные гиганты